2021
DOI: 10.3991/ijim.v15i07.21561
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Interactive Multimedia Software “Inquiry Play-Room” as an Electronic Learning Resource for Rotation and Equilibrium Topic

Abstract: This study reports the development of the interactive electronic multimedia “Inquiry Play-Room” for use in rotation and equilibrium topics. This was designed following the steps of a guided inquiry laboratory model, containing video problems, feedback, virtual laboratories, student worksheets, animations, practical applications, and quizzes. The tests are offered at two levels, one to grasp the concept and the second to be incorporated into actual life. This difference in learning can spur student confidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nevertheless, no research has been found to utilize ICT into preparedness learning with viral laboratory formats to enhance skill problem solving of vocational students (Hoesni et al, 2020;Som, 2021). As one of the topics considered sufficiently demanding skills to solve contextual problems, the combination of archival material and ICT is expected to provide students with the option to practice and learn interactively (Salma Aprianka, 2020; V. S. Sari et al, 2021). It also gives students greater hope of acquiring skillsskills that are needed in the 21st century (Habibi & Suparman, 2020;Yulianisa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, no research has been found to utilize ICT into preparedness learning with viral laboratory formats to enhance skill problem solving of vocational students (Hoesni et al, 2020;Som, 2021). As one of the topics considered sufficiently demanding skills to solve contextual problems, the combination of archival material and ICT is expected to provide students with the option to practice and learn interactively (Salma Aprianka, 2020; V. S. Sari et al, 2021). It also gives students greater hope of acquiring skillsskills that are needed in the 21st century (Habibi & Suparman, 2020;Yulianisa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The editing process is the initial process in making multimedia presentations that are very dependent on the user interface on multimedia authoring tools. The editing process is the initial process in making multimedia presentations that are very dependent on the user interface on multimedia authoring tools [18]. Ease in the editing process is the first thing that an author pays attention to, various ways have been attempted and researched to increase the ease of making multimedia presentations [19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the development of information technology plays a very important role in the world of education, for example the use of computers, smartphones, as tools to run learning media (Syahputra & Maksum, 2020;Raji, 2019;Qodr et al, 2021). Interactive media is one of the learning media that has the potential to be developed, this is because interactive media will certainly have components contained in it such as text components, sounds, images, videos, animations and even assignments/practice questions (Sari et al, 2021;Syahputra & Maksum, 2020), so that it clearly describes the material in the learning process.…”
Section: Introductionmentioning
confidence: 99%